Post‐operative outcomes in anonymous living liver donors: What motivates individuals to donate to strangers. Issue 10 (23rd September 2021) - Flaig, Carly; Humar, Abhinav; Kirshner, Emily; Hughes, Christopher; Ganesh, Swaytha; Tevar, Amit; Steel, Jennifer L.
Abstract: Background: Anonymous living donor liver transplantation (LDLT) is a strategy to address the shortage of available transplantable livers; however, few studies have been conducted on this population. The objective of this study was to describe the motivations and medical, psychosocial, and financial outcomes of anonymous living liver donors. Methods: Between 2010–2019, 116 anonymous living liver donors were evaluated, 59 (51.7%) of whom proceeded to surgery. A subset of 21 anonymous donors were matched to biologically/emotionally related donors according to age, gender, race, and duration since surgery. A medical chart review and post‐surgical interviews were performed to assess medical and financial outcomes. Results: The primary motivation for donors was an unselfish desire to help others (43, 72.9%). A total of 13 (22%) anonymous donors experienced complications. Of these, 7 (11.9%) were grade I Clavien‐Dindo classification, 5 (8.5%) grade II, 1 was grade III (1.7%); and no patients had grade IV–V Clavien‐Dindo complications. Increased anxiety was reported by 3 (5.1%) donors, and one donor reported clinical levels of depression (1.7%). Within the matched controls, anonymous donors were not significantly different to biologically/emotionally related donors with regard to surgical complications, psychosocial, or financial outcomes. Conclusions: Allowing a greater number of anonymous donors may facilitate the reduction of the waitlist for liver transplant candidates.